Looking for Justice: Can labour law help ti find it? - Salas-Porras, María; Aguirre-de-Mena, Juan Martín (My University, 2015)
This presentation represents a reflection about the importance of justice in our societies. In this sense, several questions help to understand whether it is useful to rethink about the role of labour law in finding and building the idea of justice inside the labour relationship.
Keywords: Trabajo - Legislación; Relaciones laborales; Relational justice; Justice; Labour law